Physical activity during pregnancy and pregnancy related complication - Molla Hailu; Natnael Amare Tesfa; Amare Nigatu; Abayneh Tunta; Zeru Seyoum; Tigabu Derbew (Scientific Reports)
Abstract Even though motherhood is a positive and enjoyable experience, it is also a vulnerable period that can be accompanied by various complications. Hypertensive disorders of pregnancy and gestational diabetes mellitus are the most significant contributors to these complications. Therefore, the main objective of this study was to assess if the degree of physical activity during pregnancy has an impact on the development of hypertensive disorder of pregnancy and gestational diabetes mellitus. In this cross-sectional study, 150 women were involved. Among the total study participants, 65(43.3%) and 85(56.7%) of them were engaged in vigorous physical activities and light physical activities during pregnancy, respectively. Of these study participants, 62 (41.3%) of them had pregnancy-related complications. It was found that women who engaged in vigorous physical activity had a lower proportion of complications (17.74%) compared to those who engaged in light physical activity (82.26%). This difference was statistically significant (p = 0.001). The finding of this study showed that pregnancy-related complications, specifically HDP and GDM, were low in women who had vigorous physical activities during pregnancy as compared to those who had a sedentary lifestyle or engaged in light physical activities.